2019
DOI: 10.1021/acs.jpclett.9b03392
|View full text |Cite
|
Sign up to set email alerts
|

Activity Origin and Design Principles for Oxygen Reduction on Dual-Metal-Site Catalysts: A Combined Density Functional Theory and Machine Learning Study

Abstract: Dual-metal-site catalysts (DMSCs) are emerging as a new frontier in the field of oxygen reduction reaction (ORR). However, there is a lack of design principles to provide a universal description of the relationship between intrinsic properties of DMSCs and the catalytic activity. Here, we identify the origin of ORR activity and unveil design principles for graphene-based DMSCs by means of density functional theory computations and machine learning (ML). Our results indicate that several experimentally unexplor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 57 publications
3
129
0
Order By: Relevance
“…combined comprehensive DFT calculations, microkinetic modeling, and ML to scrutinize possible ORR descriptors for TM 2 ‐N 6 ‐C DACs (Figure 11d). [ 52a ] Using DFT calculations, they found a linear scaling relationship between Δ G OH* and Δ G OOH* (Figure 11e) and also found that Δ G OH* can act as an independent descriptor to describe the ORR activity of DACs. Nevertheless, it would be more intuitive if the ORR activity for DACs can be predicted even prior to the intensive DFT calculations because of its high computational cost.…”
Section: Practical Applications Of Dacs In Heterogeneous Catalysismentioning
confidence: 99%
See 3 more Smart Citations
“…combined comprehensive DFT calculations, microkinetic modeling, and ML to scrutinize possible ORR descriptors for TM 2 ‐N 6 ‐C DACs (Figure 11d). [ 52a ] Using DFT calculations, they found a linear scaling relationship between Δ G OH* and Δ G OOH* (Figure 11e) and also found that Δ G OH* can act as an independent descriptor to describe the ORR activity of DACs. Nevertheless, it would be more intuitive if the ORR activity for DACs can be predicted even prior to the intensive DFT calculations because of its high computational cost.…”
Section: Practical Applications Of Dacs In Heterogeneous Catalysismentioning
confidence: 99%
“…Owing to the relatively low computational cost, microkinetic modeling can open up new pathways for analyzing experimental results and provide predicting power; thus, it can act as a powerful tool for probing the catalytic activity of DACs. [ 52 ]…”
Section: Exploration Of Dacs By Theoretical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several early reviews have introduced the applications of ML to materials science, including materials discovery and design, catalysts, and structure prediction . Very recently, ML investigations on energy storage and conversion materials have rapidly increased, which have not been comprehensively summarized.…”
Section: Introductionmentioning
confidence: 99%